Role of different Pfcrt and Pfmdr-1 mutations in conferring resistance to antimalaria drugs in Plasmodium falciparum - Ibraheem, Zaid O.; Abd. Majid, Roslaini; Mohd. Noor, Sabariah; Mohd. Sedik, Hasidah; Basir, Rusliza (Hindawi Publishing Corporation, 2014)
Emergence of drugs resistant strains of Plasmodium falciparum has augmented the scourge of malaria in endemic areas. Antimalaria drugs act on different intracellular targets. The majority of them interfere with digestive vacuoles (DVs) while others affect other organelles, namely, apicoplast and mitochondria. Prevention of drug accumulation or access into the target site is one of the mechanisms that plasmodium adopts to develop resistance. Plasmodia are endowed with series of transporters that shuffle drugs away from the target site, namely, pfmdr (Plasmodium falciparum multidrug resistance transporter) and pfcrt (Plasmodium falciparum chloroquine resistance transporter) which exist in DV membrane and are considered as putative markers of CQ resistance. They are homologues to human P-glycoproteins (P-gh or multidrug resistance system) and members of drug metabolite transporter (DMT) family, respectively. The former mediates drifting of xenobiotics towards the DV while the latter chucks them outside. Resistance to drugs whose target site of action is intravacuolar develops when the transporters expel them outside the DVs and vice versa for those whose target is extravacuolar. In this review, we are going to summarize the possible pfcrt and pfmdr mutation and their role in changing plasmodium sensitivity to different anti-Plasmodium drugs.